Comparison of Blockbuster LMA with Air Q LMA for Success of Blind Tracheal Intubation in Patients Undergoing General Anesthesia - Endigeri, Archana; Hulakund, Shivanand; Rajanna, Raghavendra; Ganeshnavar, Anilkumar; Kelageri, Satish; Teja, Palluri Sai (Journal of Anaesthesia and Pain, 2023)
Background: Blockbuster Laryngeal mask airway (LMA) is a device gaining popularity in airway management, and advantageous in ventilation and intubation. Air Q LMA is a supraglottic airway device with a shorter and wider breathing tube designed for ventilation as well as intubation in difficult airway. We aimed to evaluate the success of tracheal intubation using these devices.Methods: Overall 80 participants aged 18-60 years with ASA I and II were randomized into Group A (Air Q LMA) and Group B (Blockbuster LMA) using computer generated random numbers. The objectives of our study were to evaluate first pass successful intubation, ease, time and attempts taken for device insertion, oropharyngeal leak pressure, time for LMA removal and post operative complications. Association between variables were assessed with chi square test and unpaired t test.Result: There was a statistically significant difference in the first pass successful intubation between the groups which was higher in Group B (90%) than Group A (60%) (P<0.001), the overall successful intubation was more in Group B 97.5% compared to Group A 85%. The device insertion was easy in 85% patients in Group A and 95% patients in Group B. The time taken for introduction of Air Q was longer (38.15±4.92sec) when compared with blockbuster LMA (26.25±4.44sec), (P<0.001).  Mean Oropharyngeal leak pressure of blockbuster LMA (32.40±3.99cmH2O) was greater than Air Q LMA (29.10±2.61cmH2O), (P<0.001).Conclusion: Blockbuster LMA provides greater success of blind tracheal intubation when compared to air Q LMA.